Genotipagem por sequenciamento para identificação de SNPs e associação com características agronômicas em Coffea canephora - Motta, Ludymila Brandão (2016)
Genotyping by sequencing (GBS) is able to identify and genotype thousands of SNP simultaneously. This work aims to contribute to the genetic improvement of Robusta coffee characterizing the occurrence of SNPs in canephora genome and studying the associati